Vocation as a primary feature in the public servant (2019)
Every public servant is given as his name says to the "service" of the state and society, he must perform his duties in accordance with the provisions of the political constitution, the law and established norms. The reason for the being of public servants is the achievement of the purposes of the state, which is why these officials are due to the community, their daily work must be motivated to the common good.